Noteworthy Literature in Cardiac Anesthesia for 2019. (June 2020) - Clendenen, Nathan; Abrams, Benjamin; Morabito, Joseph; Grae, Lyndsey; Mosca, Matthew S.; Weitzel, Nathaen
This article represents a selective review of literature published in 2019. Initial results from PubMed searching for a combination of terms, including cardiac anesthesiology and anesthesiology outcomes, yielded more than 1400 publications. From there, we manually screened the results and identified 5 major themes for the year of 2019, including transcatheter techniques, delirium and anesthesiology, coagulation management following cardiopulmonary bypass, perfusion management with del Nido cardioplegia, and applied clinical research . The following research accomplishments have expanded what is possible and set ambitious goals for the future.